New directions in the fight against antibiotic resistance - Mihai Folescu; Eugenia Dumitrescu; Florin Muselin; Alexandru Octavian Doma; Daiana Ionela Cocoș; Larisa Ardelean; Romeo Teodor Cristina (Medicamentul Veterinar)
Antibiotics have transformed medicine, enabling effective treatments for infections that were once fatal and supporting significant advancements such as surgery and organ transplants. However, the growing spread of resistance reduces their effectiveness, making the discovery of new drugs crucial in the ongoing battle against human pathogens. Antibiotic resistance represents one of the greatest challenges of modern medicine, having a significant impact on the treatment of bacterial infections. The development of antibiotic resistance renders standard treatments ineffective, putting patients' lives at risk and limiting available therapeutic options. In the face of this global crisis, recent research is opening new directions in combating antibiotic resistance, focusing on the discovery of innovative antibiotics, alternative solutions, and strategies to prevent the spread of resistance. These advances are essential for addressing future health challenges.